Book review: Votes for housing: the case of a mobilized clientele. San José Nacional 1980-1990 by Patricia E. Badilla Gómez and José M. Cerdas Albertazzi - Delgado Rojas, Jaime (2019)
The book that concerns us is the result of important research in the field of sociology and political history, very well grounded not only theoretically, but also in the analysis of the reality that it deals with.